(untitled) (SCIÉNDO INGENIUM, 2022)
The present study sought to establish the influence of the implementation of an Environmental Education Program (PEA) in the reduction of the amount of waste generated in the direct areas, municipalities and communities surrounding Sections I and II of the concessioned highway Empalme Ruta1B-Buenos Aires-Canchaque in Piura, in evidence of bad habits in the right-of-way that originate the need for a greater deployment of cleaning activities and an optimal process to stop its transformation into a garbage dump. The research design is pre-experimental - explanatory and the sample is composed of 321 homes selected by means of probabilistic sampling, to which the pre-test and post-test evaluation was applied, in the nature of environmental education and measurement of the amount of waste. To measure the degree of knowledge on environmental issues, a semi-structured and closed questionnaire on a Likert scale was used and the instruments were validated through expert judgment; concluding that the implementation of the PEA directly influences the reduction of solid waste, the creation of strategic alliances in environmental matters, the modification of habitual pernicious behavior, prevention, conservation, protection and restoration of the environment, thus structuring a new environmental culture.